Reclaiming Subsidized Land: An Evaluation of Coal Gangue Interlayers - Yuling Gong; Zhenqi Hu; Kevin McSweeney (Advances in Materials Science and Engineering)
Rehabilitation of areas impacted by subsidence following coal mining is a pressing need in eastern China, especially where availability of suitable soil material is limited. A field experiment was established to evaluate performance of varying layered combinations of soil and coal gangue materials as measured by maize (Zea mays L.) growth and yield. Two control treatments and eight experimental treatments were constructed. All treatments had a 30 cm surface layer of topsoil. CK1 consisted of native soil material. CK2 consisted of 50 cm gangue covered by topsoil and 40 cm subsoil. Group 1 treatments (T1–T3) had a 15 cm layer of subsoil immediately below the topsoil, underlain, respectively, by progressively thicker gangue layers (20, 30, and 40 cm) overlying another 15 cm subsoil layer, in turn underlain by gangue. Group 2 treatments (T4–T7) consisted of 40 cm subsoil. T4-T5 followed the same pattern as Group 1 except that the lower subsoil layer was 25 cm thick. T6-T7 differed from T4-T5 by having 25 cm upper and 15 cm lower subsoil layers between different thicknesses of gangue. Group3 (T8) consisted of three 10 cm layer of subsoil separating 2 gangue layers and gangue layer below. Key plant performance indicators, biomass and yield, were significantly better under CK1-2 than in the other treatments (T1–T8). Below the topsoil Eh, pH and total salt content were higher and water content was less in T1–T8 than in CK1-2, reflecting the influence of gangue in 30–70 cm zone in these treatments. The nutrient content (TN, AN, TP, OP, TK, AK, and OM) of topsoil in experimental treatments was lower than or similar to that of the control treatments. Results indicate that minimizing the adverse impacts of gangue requires a combined top-subsoil cover of at least 70 cm.